Genetic counseling for pre-implantation genetic testing of monogenic disorders (PGT-M) - Parikh, Firuza; Athalye, Arundhati; Madon, Prochi; Khandeparkar, Meenal; Naik, Dattatray; Sanap, Rupesh; Udumudi, Anuradha (Frontiers in Reproductive Health, 2023)
Pre-implantation genetic testing (PGT) is a vital tool in preventing chromosomal aneuploidies and other genetic disorders including those that are monogenic in origin. It is performed on embryos created by intracytoplasmic sperm injection (ICSI). Genetic counseling in the area of assisted reproductive technology (ART) has also evolved along with PGT and is considered an essential and integral part of Reproductive Medicine. While PGT has the potential to prevent future progeny from being affected by genetic conditions, genetic counseling helps couples understand and adapt to the medical, psychological, familial and social implications of the genetic contribution to disease. Genetic counseling is particularly helpful for couples with recurrent miscarriages, advanced maternal age, a partner with a chromosome translocation or inversion, those in a consanguinous marriage, and those using donor gametes. Partners with a family history of genetic conditions including hereditary cancer, late onset neurological diseases and with a carrier status for monogenic disorders can benefit from genetic counseling when undergoing PGT for monogenic disorders (PGT-M). Genetic counseling for PGT is useful in cases of Mendelian disorders, autosomal dominant and recessive conditions and sex chromosome linked disordersand for the purposes of utilizing HLA matching technology for creating a savior sibling. It also helps in understanding the importance of PGT in cases of variants of uncertain significance (VUS) and variable penetrance. The possibilities and limitations are discussed in detail during the sessions of genetic counseling.